Counseling and Training on Early Detection and Initial Handling of Acute Heart Failure for Health Workers in Emergency Installations - Ronny Ajartha (JURNAL PENGMAS KESTRA (JPK), 2024)
Acute heart failure (AHF) is a serious medical condition that requires immediate management, as it can lead to high morbidity and mortality if not detected and treated promptly. Early detection of AHF is crucial in improving patient prognosis, reducing complications, and minimizing the risk of death. Health education on early detection of acute heart failure is essential for healthcare workers, especially in Emergency Departments (ED), who are at the frontline of managing patients with emergency symptoms. This educational effort aims to raise awareness about the early symptoms of AHF, such as shortness of breath, excessive fatigue, swelling, and chest pain, as well as recognizing the risk factors that can lead to AHF, such as hypertension, diabetes, and a history of heart disease. With a better understanding of the symptoms and risk factors, healthcare professionals in the ED are expected to make faster diagnoses using appropriate diagnostic tools like electrocardiograms (ECG), echocardiography, and biomarker testing. Early detection education also plays a vital role in informing the public about the importance of recognizing symptoms and seeking prompt medical care. Therefore, structured early detection education on acute heart failure will improve healthcare quality in the ED, accelerate patient management, and ultimately reduce mortality rates associated with acute heart failure.